Searching for the Genus Epidemicus in Chinese Patients: Findings from the Clificol COVID-19 Clinical Case Registry - Tournier, Alexander; Fok, Yvonne; van Haselen, Robbert; To, Aaron (Homeopathy, 2022)
Background The Clificol COVID-19 Support Project is an innovative international data collection project aimed at tackling some of the core questions in homeopathy. This paper reports on the further investigation of the genus epidemicus concept during the first wave of the pandemic in the Chinese population.Methods The design is an observational clinical case registry study of Chinese patients with confirmed or suspected coronavirus disease 2019 (COVID-19). The symptoms were prospectively collected via a 150-item questionnaire. The concept of genus epidemicus, including the role of treatment individualization, was investigated by analyzing whether presenting symptoms clustered into distinct groups. Two standard statistical analysis techniques were utilized: principal component analysis for extracting the most meaningful symptoms of the dataset; the k-means clustering algorithm for automatically assigning groups based on similarity between presenting symptoms.Results 20 Chinese practitioners collected 359 cases in the first half of 2020 (766 consultations, 363 prescriptions). The cluster analysis found two to be the optimum number of clusters. These two symptomatic clusters had a high overlap with the two most commonly prescribed remedies in these sub-populations: in cluster 1 there were 297 prescriptions, 95.6% of which were Gelsemium sempervirens; in cluster 2 there were 61 prescriptions, 95.1% of which were Bryonia alba.Conclusion This is the first study to investigate the notion of genus epidemicus by using modern statistical techniques. These analyses identified at least two distinct symptom pictures. The notion of a single COVID-19 genus epidemicus did not apply in the studied population.
Keywords: genus epidemicus; COVID-19; clinical case registry